Development of a fuzzing tool for a mobile phone browser - Soo, Jian Wei. (2012)
With the increase in number of people relying on mobile devices in their everyday lives, the more enticing these devices become targets to thieves and other nefarious types. In recent years, IT security researchers have expressed rising concerns over